An econometric analysis of the costs of rain-fed olive production in Syria - سليمان حيان (Latakia University Journal -Biological Sciences Series, 2023)
The research aimed to study the development of production costs per hectare of rain-fed olives at the country level during the period (2011-2019) and to determine the optimal size of production achieving economic efficiency through standard analysis of the functions of production costs per kilogram of rain-fed olives during the period studied. The research was carried out at the level of the Syrian Arab Republic, depending on the annual agricultural statistical collections during the period (2011-2019).In this research, the descriptive analytical approach was relied upon to study the development of production costs during the studied period and to estimate the relative importance of each item by using tables, percentages and index numbers. Logistic) to explain the relationship between the amount of output as an independent variable and the amount of production costs as a dependent variable. The research results showed that the cost of one kilogram of olives reached its highest value in the year (2019) at about 390.96 SP / kg, with a record number of 919.90% compared to the year (2011), an increase of 819.90% compared to the year 2011. The costs of agricultural operations occupied about 49.71% of the total production costs per hectare. Harvesting costs constituted the highest percentage in terms of the costs of agricultural operations, due to its reliance on high-paid labor. On the other hand, the costs of production requirements accounted for 29.91% of the total costs, Chemical fertilizers occupied the greatest relative importance with 63.01% of the total cost of production requirements, followed by the value of organic fertilizers with 20.92%, and containers with 10.92% ,The results of the comparison between standard models showed that the best model that expresses the relationship between production as an independent variable and costs as a dependent variable is the logistic model ,The results also indicated that the volume of actual production was far from the volume of production that achieved economic efficiency, as the optimal volume achieved for economic efficiency was 1020 kg / h.